C60-Adsorbed Single-Walled Carbon Nanotubes as Metal-Free, pH-Universal, and Multifunctional Catalysts for Oxygen Reduction, Oxygen Evolution, and Hydrogen Evolution - Gao, Rui; Dai, Quanbin; Du, Feng; Yan, Dongpeng; Dai, Liming (Journal of the American Chemical Society, 2019)
Buckminsterfullerene (C60) was adsorbed onto single-walled carbon nanotubes (SWCNTs) as an electron-acceptor to induce intermolecular charge-transfer with the SWCNTs, leading to a class of new metal-free C60-SWCNT electrocatalysts. For the first time, these newly developed C60-SWCNTs were demonstrated to act as trifunctional metal-free catalysts for oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) over a wide range of pH values, from acid to alkaline, with even higher electrocatalytic activities and better long-term stabilities than those of commercial Pt and RuO2 counterparts. Thus, the adsorption-induced intermolecular charge-transfer with the C60 electron-acceptor can provide a general approach to high-performance, metal-free, pH-universal carbon-based trifunctional metal-free electrocatalysts for water-splitting and beyond.